Canine and feline behavioral therapy - Hart, Benjamin L. (Blackwell Pub., 2006)
Canine and Feline Behavior Therapy, Second Edition offers practical advice from board-certified specialists applicable to any small animal practice. This edition includes revisions based on major advances in the clinical animal behavior field and is written at a level to appeal to veterinary students, canine and feline practitioners, and veterinary behaviorists.